Challenges and considerations in determining the quality of electronic performance & tracking systems for team sports - Robertson, Sam; Duthie, Grant Malcolm; Ball, Kevin; Spencer, Bartholomew; Serpiello, Fabio Rubens; Haycraft, Jade; Evans, Nicolas; Billingham, Johsan; Aughey, Robert James (Frontiers in Sports and Active Living, 2023)
Electronic performance & tracking systems (EPTS) are commonly used to track the location and velocity of athletes in many team sports. A range of associated applications using the derived data exist, such as assessment of athlete characteristics, informing training design, assisting match adjudication and providing fan insights for broadcast. Consequently the quality of such systems is of importance to a range of stakeholders. The influence of both systematic and methodological factors such as hardware, software settings, sample rate and filtering on this resulting quality is non-trivial.Highlighting these allows for the user to understand their strengths and limitations in various decisionmaking processes, as well as identify areas for research and development. In this paper, a number of challenges and considerations relating to the determination of EPTS validity for team sport are outlined and discussed. The aim of this paper is to draw attention of these factors to both researchers and practitioners looking to inform their decision-making in the EPTS area. Addressing some of the posited considerations in future work may represent best practice; others may require further investigation, have multiple potential solutions or currently be intractable.